2022
DOI: 10.3390/ma15238660
|View full text |Cite
|
Sign up to set email alerts
|

Low Core Losses of Fe-Based Soft Magnetic Composites with an Zn-O-Si Insulating Layer Obtained by Coupling Synergistic Photodecomposition

Abstract: The major method used to reduce the magnetic loss of soft magnetic composites (SMCs) is to coat the magnetic powder with an insulating layer, but the permeability is usually sacrificed in the process. In order to achieve a better balance between low losses and high permeability, a novel photodecomposition method was used in this study to create a ZnO insulating layer. The effect of the concentration of diethyl zinc on the formation of a ZnO insulating film by photodecomposition was studied. The ZnO film was be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Wang et al reported a novel photodecomposition method to create a ZnO insulating layer on FeSiAl powders [ 5 ]. Combined with conventional coupling treatment processes, a thin and dense Zn-O-Si insulating layer was coated on the surface of iron powder in situ.…”
Section: Soft Magnetic Alloys and Compositesmentioning
confidence: 99%
“…Wang et al reported a novel photodecomposition method to create a ZnO insulating layer on FeSiAl powders [ 5 ]. Combined with conventional coupling treatment processes, a thin and dense Zn-O-Si insulating layer was coated on the surface of iron powder in situ.…”
Section: Soft Magnetic Alloys and Compositesmentioning
confidence: 99%